Fostering Religious Moderation Through Learning English at Pesantren Ma'had Aly - Abu Ali Al-Khusain (Journal of English Language Teaching and English Linguistics, 2022)
This research was aimed at two progressive aspects, namely improving speaking and giving awareness towards moderation. The subjects were 21 students of the first semester students of Ma'had Aly Pondok Pesantren Krapyak Yogyakarta. The data were collected using questionnaires, observation, and tests and were analyzed descriptively and quantitatively. The topic of moderation in the student's real life and knowledge effectively improved the speaking learning process. It also triggers the students to express their ideas about moderation. The findings showed that it improved the learning process of speaking. They actively participated in group discussions to present their opinion and propose solution. The students were confident in speaking English. The improvement of students speaking skills was proven by the increase in the test results. The students’ average score in the pre-test was 65, while in cycle one was 71 and 82 in cycle two.